Estimating dew duration on banana and plantain leaves from standard meteorological observations - Lhomme, Jean-Paul; Jiménez Otárola, Francisco (Elsevier (Amsterdam), 2016)
Black Sigatoka is an important fungal disease of bananas and plantains. Dew duration on the upper leaves of these plants (Leaves O and 1) is an important factor in the development of the disease. A general dew estimation scheme, based on an energy budget approach, WAS adapted to the particular case of banana and plantain upper leaves in order to provide a tool for Black Sigatoka management. This scheme allows the estimation of dew duration from standard weather station measurements of air temperature and humidity, wind velocity, solar radiation and cloud cover. Values of dew duration estimated by this scheme were compared with observed values on plantain during 18 nights. On average, the differences between observed and estimated values were less than 1 h..